2017
DOI: 10.1080/09546634.2016.1254145
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tumor necrosis factor inhibitor therapy on the incidence of myocardial infarction in patients with psoriasis: a retrospective study

Abstract: The use of TNF inhibitors in psoriasis showed a significant reduction in the risk of MI compared with topical agents and a non-significant reduction compared with MTX. Responders to TNF inhibitor therapy showed a reduction in MI rate compared with non-responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Compared to patients who received topical therapy, psoriasis patients treated with TNF-α inhibitors showed a significant decrease in the risk of myocardial infarction (hazard ratio 0.50) [ 263 ]. Other studies have also confirmed the beneficial effects of TNF-α inhibitors in reducing the risk of myocardial infarction in psoriasis patients [ 264 , 265 , 266 , 270 , 271 , 272 ]. In addition, a number of studies have shown that treatment of psoriasis patients with TNF-α inhibitors leads to decreased risk of cardiovascular events compared to methotrexate, and greater risk reduction was found with longer duration of anti-TNF-α treatment [ 267 , 273 ].…”
Section: Effects Of Anti-psoriasis Therapies On Cardiovascular Commentioning
confidence: 77%
“…Compared to patients who received topical therapy, psoriasis patients treated with TNF-α inhibitors showed a significant decrease in the risk of myocardial infarction (hazard ratio 0.50) [ 263 ]. Other studies have also confirmed the beneficial effects of TNF-α inhibitors in reducing the risk of myocardial infarction in psoriasis patients [ 264 , 265 , 266 , 270 , 271 , 272 ]. In addition, a number of studies have shown that treatment of psoriasis patients with TNF-α inhibitors leads to decreased risk of cardiovascular events compared to methotrexate, and greater risk reduction was found with longer duration of anti-TNF-α treatment [ 267 , 273 ].…”
Section: Effects Of Anti-psoriasis Therapies On Cardiovascular Commentioning
confidence: 77%
“…For example, treatment with TNF inhibitors in rheumatoid arthritis, an overt inflammatory disease, is associated with a decreased risk of cardiovascular events 182–187 . Treatment with TNF inhibitors in psoriasis is also associated with decreased incidence of major adverse cardiac events 186,188,189 . However, anti-inflammatory treatment does not always yield beneficial effects.…”
Section: Consequences Of Inflammageing For Cvdmentioning
confidence: 99%
“…On the other hand, TNF-α inhibitors have been shown to significantly reduce the risk of myocardial infarction in patients with psoriasis compared with topical treatment. 13 In this study, infliximab was discontinued in two patients because of cerebrovascular disease in one patient and myocardial infarction in another. We think that this situation, which is contrary to the literature, may be related to the fact that both patients are elderly and diabetic and infliximab is more frequently preferred in our clinic.…”
Section: Discussionmentioning
confidence: 98%